Using Android to Set Fan Spin - Jamaaluddin, Jamaaluddin (Universitas Muhammadiyah Yogyakarta, 2020)
The Android operating system on smartphones has developed rapidly and become a favorite among other operating systems. In addition to applications that can be obtained for free, making applications on Android is also easy because the platform is open source. Hence, it allows users to create or develop applications already available. By utilizing convenience, Android smartphones can be used to control household appliances such as fans. Applications on Android can be made with the MIT App Inventor software, so it can be used to adjust the fan spin. Android applications can ease users to increase or decrease the spin speed of the fan from a distance. Arduino Nano microcontroller and Relay were used to adjust the fan spin, while the Bluetooth Module was used to connect the microcontroller and Android smartphone. After the testing process, the fan spin could be set using Android with a maximum distance of 15.2 meters without barriers and 11 meters with a wall barrier. Fan spin has 3 speed, 1473 rpm for high spin, 1462 rpm for medium spin, 1451 rpm for low spin, while the timer used consisted of 10 minutes, 20 minutes, 30 minutes, 60 minutes, and 120 minutes.